If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3(x-4)=5/4-7x
We simplify the equation to the form, which is simple to understand
2/3(x-4)=5/4-7x
Simplifying:
+ 0.666666666667*(x-4)=5/4-7x
Simplifying:
+ 0.666666666667*(x-4)=+1.25-7x
Reorder the terms in parentheses
+( + 0.666666666667x-2.66666666667)=+1.25-7x
Remove unnecessary parentheses
+ 0.666666666667x-2.66666666667=+1.25-7x
We move all terms containing x to the left and all other terms to the right.
+ 0.666666666667x+7x=+1.25+2.66666666667
We simplify left and right side of the equation.
+7.66666666667x=+3.91666666667
We divide both sides of the equation by 7.66666666667 to get x.
x=0.510869565218
| 5(2x-4)+10=5x+35 | | 5+2r=2r+6 | | 0.98(8)-1.04p=0.98(8+p) | | 3(2x-2)-9=-x+34 | | 7a-3=3+6n | | 30=5(x+2) | | 0.98(8)+1.04p=0.98(8+p) | | 3(2x-1)-3=48 | | 2(x-1)=-x+16 | | -x-9=3x+11 | | -x+47=4(x-2) | | -7x-3x+2=-8 | | 2x^2+4y^2-4x-24y+36=0 | | (2x-3)/7=(3x)/7-2x | | p^3-4p^2-p+4= | | 2.2q-3.9-2.8q=-1.6q-1.8 | | 4n=m(5-n) | | 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= |